Research-Based Learning’s Contribution Toward Achievement Motivationin Indonesia's Superior Madrasahs - Bulan, Sri; Sugianto, Hendi; Rusydiyah, Evi Fatimatur; Agustina, Andre (Universitas Islam Negeri Raden Intan Lampung, 2024)
Research-based learning in superior madrasas is prepared as a means to instill love of knowledge and empathy for the environment and encourage students to reason critically, creatively and independently which is the principle in the independent curriculum. This study aims to examine the contribution of research-based learning at MAN Insan Cendekia Pekalongan to student achievement motivation. The research method used is qualitative with data collection techniques through unstructured interviews, field observations, and documentation. In addition, research instruments were given to 95 students who became the initial population of the study using google forms to ensure the possibility of diversity of perspectives on research-based learning and motivation for achievement. Furthermore, data collection was carried out by purposive sampling to 17 students who participated in the preparation of the national scientific paper competition to dig up achievement data for achievement (nAch) in depth. The results of the study showed that there was a significant contribution of research-based learning to students' motivation for achievement which was shown by the desire to do something more than ordinary learning (nAch1), the desire to solve problems in research (nAch2), the desire to take personal responsibility in research (nAch3), and the desire to show good performance in research (nAch4). Overall, RbL contributes to facilitating students to think critically, creatively and independently which is part of the expected character in the independent curriculum.